2018
DOI: 10.1007/s00221-018-5311-6
|View full text |Cite
|
Sign up to set email alerts
|

Hand anthropometry and the limits of aperture separation determine the utility of Weber’s law in grasping and manual estimation

Abstract: Recent work proposed that biomechanical constraints in aperture separation limit the utility of Weber's law in determining whether dissociable visual codes support grasping and manual estimation. We tested this assertion by having participants precision grasp, manually estimate and complete a method of adjustment task to targets scaled within and beyond the range of their maximal aperture separation (i.e., from 20 to 140% of participant-specific maximal aperture separation: MAS). For grasping and manual estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…This result provides a direct replication of Ganel et al (2012) and supports the PAM's assertion that the dorsal pathway provides the visuomotor system absolute visual information to mediate metrically precise hand-target interactions (for review, see Goodale & Milner, 2018). Thus, the present findings, PANTOMIME-GRASPS AND VISUAL RESOLUTION those of Ganel et al (2012) and the extant grasping literature (for reviews, see Goodale, 2011;Smeets & Brenner, 1999) demonstrate that PGAs scale to veridical target size across stimuli that are below-and above (see Ayala et al, 2018;-the Weber's fraction for the discrimination of line length. Notably, however, pantomime-grasp PGAs for the 40.0 mm and 40.5 mm targets did not reliably differ and a TOST statistic indicated that values were within an equivalence boundary.…”
Section: Discussionsupporting
confidence: 86%
“…This result provides a direct replication of Ganel et al (2012) and supports the PAM's assertion that the dorsal pathway provides the visuomotor system absolute visual information to mediate metrically precise hand-target interactions (for review, see Goodale & Milner, 2018). Thus, the present findings, PANTOMIME-GRASPS AND VISUAL RESOLUTION those of Ganel et al (2012) and the extant grasping literature (for reviews, see Goodale, 2011;Smeets & Brenner, 1999) demonstrate that PGAs scale to veridical target size across stimuli that are below-and above (see Ayala et al, 2018;-the Weber's fraction for the discrimination of line length. Notably, however, pantomime-grasp PGAs for the 40.0 mm and 40.5 mm targets did not reliably differ and a TOST statistic indicated that values were within an equivalence boundary.…”
Section: Discussionsupporting
confidence: 86%
“…Another seemingly challenging finding for the biomechanical account was recently reported by Ayala et al (2018). In this study, they used object sizes that were adjusted to the size of participants’ hands.…”
Section: Introductionmentioning
confidence: 87%
“…Given the ubiquity of Weber's law it was very astounding when researchers reported that grasping—a central human ability—does not obey Weber's law ( Ganel et al., 2008 ). The main experimental result leading to this claim has been replicated many times, and far-reaching theoretical consequences for the understanding of the functional architecture of the brain were derived ( Ayala, Binsted, & Heath, 2018 ; Christiansen, Christensen, Grünbaum, & Kyllingsbæk, 2014 ; Freud, Culham, Namdar, & Behrmann, 2019 ; Ganel et al., 2008 ; Hadad, Avidan, & Ganel, 2012 ; Heath, Mulla, Holmes, & Smuskowitz, 2011 ; Heath, Holmes, Mulla, & Binsted, 2012 ; Heath, Manzone, Khan, & Davarpanah Jazi, 2017 ; Heath & Manzone, 2017 ; Holmes, Mulla, Binsted, & Heath, 2011 ; Holmes & Heath, 2013 ; Hosang, Chan, Jazi, & Heath, 2016 ; Jazi & Heath, 2017 ; Löwenkamp, Gärtner, Haus, & Franz, 2015 ; Namdar, Algom, & Ganel, 2018 ; Ozana, Berman, S., & Ganel, 2018 ; Ozana & Ganel, 2017 ; Ozana & Ganel, 2018 ; Utz, Hesse, Aschenneller, & Schenk, 2015 ).…”
Section: Introductionmentioning
confidence: 87%
“…First, we conducted our experiment with a grasping and a manual estimation task. The design was optimized to investigate Weber's law: (a) we minimized biomechanical constraints by using functionally “graspable” object sizes between 20 and 50 mm ( Ayala et al., 2018 ; Heath & Manzone, 2017 ; Heath et al., 2017 ); (b) each object was repeated 50 times (instead of the usual ≤20 repetitions in such experiments; cf. Appendix D ) to improve the parameter estimates; and (c) we used a relatively large sample size of N = 20 participants.…”
Section: Experiments 1: Weber's Law In Grasping and Manual Estimationmentioning
confidence: 99%